Ruminal Degradability and Bypass Nutrients of Alkaline or Steam-Treated Cassava Chip and Corn Grain - Srakaew, W.; Wachirapakorn, C.; Cherdthong, A.; Wongnen, C. (Tropical Animal Science Journal, 2021)
Modification of starches in high-energy feeds using various treatment methods led to the diverse effects on ruminal degradation and bypass protein and starch. Thus, the objectives of the present experiment were to investigate the effects of modification methods applied to high-starch energy feed sources on ruminal degradability and bypass nutrients determined using in situ and in vitro gas production techniques. This experiment was designed using a 2×4 factorial arrangement in a completely randomized design (CRD). The first factor was high-starch energy feed consisted of two levels, i.e., corn grain and cassava chips. The second factor was the treating method consisted of four levels, i.e., no treatment, steam treatment, NaOH treatment, and steam with NaOH treatment. Chemical composition, ruminal in situ disappearance, bypass of crude protein (CP) and non-fiber carbohydrate (NFC), and gas production characteristics were measured in pre-treated and post-treated samples. The results showed that significant interactions (p